Comparative Study of Rankine Cycle Power Generation using Water and Organic Fluids in Saturated and Superheated States - Pikra, Ghalya; Sudibyo, Henny (Makara Journal of Technology, 2021)
The Rankine cycle is an electricity generation system that uses water or organic fluids as high-grade or low-grade heat sources, respectively. In this paper, we present the results of our study of Rankine-cycle power generation in which we compared water and organic fluids (toluene and n-nonane) as working fluids in saturated and superheated states. We analyzed the energy and exergy of the Rankine cycle in a saturated vapor state at 300 °C and superheated states at 400 °C and 500 °C (the pressure remained the same as that at 300 °C), and assumed a constant heat input for all states. In the energy analysis, we determined the mass flow rate, heat rejection, work input of the pump, work generated by the turbine, net work output, and thermal efficiency. In the exergy analysis, we determined the exergy input, exergy loss, exergy destruction at the pump and the turbine, and the exergetic efficiency. The results show that water, categorized as a wet fluid, obtains a better performance with respect to both analyses in saturated and superheated states than toluene and n-nonane, which are categorized as isentropic and dry fluids, respectively. The water realizes a higher performance in the superheated than in the saturated state, whereas the performances of toluene and n-nonane are poorer in the superheated than in the saturated state.